Construction of a Nanoporous Highly Crystalline Hexagonal Boron Nitride from an Amorphous Precursor for Catalytic Dehydrogenation. Issue 31 (27th June 2019) - Chen, Hao; Yang, Zhenzhen; Zhang, Zihao; Chen, Zitao; Chi, Miaofang; Wang, Song; Fu, Jie; Dai, Sheng
Abstract: Hexagonal boron nitride (h‐BN) is regarded as a graphene analogue and exhibits important characteristics and vast application potentials. However, discovering a facile method for the preparation of nanoporous crystalline h‐BN nanosheets (h‐BNNS) is still a challenge. Herein, a novel and simple route for the conversion of amorphous h‐BN precursors into highly crystalline h‐BNNS was achieved through a successive dissolution–precipitation/crystallization process in the presence of magnesium. The h‐BNNS has high crystallinity, high porosity with a surface area of 347 m 2  g −1, high purity, and enhanced thermal stability. Improved catalytic performance of crystalline h‐BNNS was evidenced by its much higher catalytic efficiency in the dehydrogenation of dodecahydro‐N‐ethylcarbazole, compared with its amorphous h‐BN precursor, as well as other precious‐metal‐loaded heterogeneous catalysts. Abstract : Highly crystalline nanoporous hexagonal boron nitride nanosheets (h‐BNNS) were prepared using amorphous h‐BN precursors through a dissolution–precipitation/crystallization process in the presence of magnesium. The crystalline h‐BNNS is a catalyst for the dehydrogenation of dodecahydro‐ N ‐ethylcarbazole.